Variations in the wood properties of Terminalia mantaly (H. Perrier) grown as municipal tree in a Nigerian university (2014)
A study was carried out b investigate wood properties of Terminalia mantaly (H. perrier), one of the municipal tree species in University of Ibadan, Ibadan. Materials for the study were obtained from four of the urban trees in the University campus. Test samples were collected at four different levels along the height and dial positions with the test specimen prepared in accordance with standard test procedures. Prepared samples were subjected to some physical and mechanical property tests. The selected physical properties were Moisture Content (MC), Specific Gravity (SG) and Volumetric Shrinkage (VS). The mechanical properties (Modulus of Rupture, MOR; Modulus of Elasticity, MOE and Impact bending, IB) were determined in accordance with the British Standard BS373 (1989), Data generated were subjected to statistical analysis. The overall mean SG, MC and VS for the species were 0.797, 39.82% and 46.52%, respectively while the mean MOR, MOE and IMB were 62.94N/mm2,5056N/mm2 and 404.81, respectively, It was evident that variations exist in both the radial directions and sampling heights for all the selected trees. Findings revealed that Terminalia mantaly is a strong wood with gaud quality, making it a potential material for load bearing and other construction work.